2014
DOI: 10.1038/cddis.2014.502
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression array in TSC2-deficient AML cells reveals IRF7 as a pivotal factor in the Rheb/mTOR pathway

Abstract: Mutations in tuberous sclerosis (TSC) genes cause the genetic disorder TSC, as well as other neoplasms, including lymphangioleiomyomatosis (LAM) and angiomyolipomas (AMLs). AMLs are benign renal tumors occur both in sporadic LAM and in TSC. As they carry the same mutations, AML cell lines serve as a model for TSC and LAM. Rheb/mammalian target of rapamycin complex 1 (mTORC1) pathway is chronically activated in TSC-deficient cells, and this activation can be diminished using the appropriate inhibitors. Rapamyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…It was reported that IRF7 was downstream target of mTOR signaling in angiomyolipoma. 36 Downregulation of mTORC1 was known to be essential for HSC selfrenewal and maintenance. [37][38][39] Inhibition of mTOR with rapamycin (an mTOR inhibitor) promoted in vitro expansion and long-term engraftment of HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that IRF7 was downstream target of mTOR signaling in angiomyolipoma. 36 Downregulation of mTORC1 was known to be essential for HSC selfrenewal and maintenance. [37][38][39] Inhibition of mTOR with rapamycin (an mTOR inhibitor) promoted in vitro expansion and long-term engraftment of HSCs.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Low expression of IRF7 can inhibit the proliferation of AML cells in human angiomyolipoma through the Rheb/mTOR pathway. 30 In breast cancer, IRF7-mediated IFN-α reduces the production of bone marrow derived suppressor cells (MDSCs) and plays an important role in bone metastasis of breast cancer by activating CD4+ cells. 31 …”
Section: Discussionmentioning
confidence: 99%
“…The IRF7 gene was originally cloned in 1997, in the context of latent Epstein–Barr virus (EBV) infection where the encoded protein binds to and regulates the EBNA1 Q promoter 18 . In human angiomyolipoma (AML) cells 621.102 and 621.103, knockdown of IRF7 in the Rheb/mTOR pathway by si-RNA inhibited the proliferation of AML cells 19 . In addition, it has been reported that ectopic expression of IRF7 in human glioma cells U87MG and LN229 directly induced the production of IL-6, which maintained glioma stem cell properties via the Janus kinase/signal transducer and activator of transcription-mediated activation of Jagged-Notch signaling 9 .…”
Section: Discussionmentioning
confidence: 99%